2022
DOI: 10.1021/jasms.2c00033
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Metal Adduction and Charge Isomerism on Ion-Mobility Measurements using m-Xylene Macrocycles as Models

Abstract: Gas-phase ion-mobility spectrometry provides a unique platform to study the effect of mobile charge(s) or charge location on collisional cross section and ion separation. Here, we evaluate the effects of cation/anion adduction in a series of xylene and pyridyl macrocycles that contain ureas and thioureas. We explore how zinc binding led to unexpected deprotonation of the thiourea macrocyclic host in positive polarity ionization and subsequently how charge isomerism due to cation (zinc metal) and anion (chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“… 1 These charge-carrying species can also affect intrinsic properties of the sample molecules, as previously reported for a range of compound classes such as carbohydrates, 2 glycans and glycopeptides, 3 steroids, 4 fullerenes, 5 and macrocycles. 5 , 6 For example, Kellner et al showed that the formation, disassembly, and stability of crown ether fullerene dimers depend on the size of the alkali metal cations used, which was attributed to different binding sites. 5 Rister et al used IM-MS to separate isobaric steroids and reported varying CCS resolutions for different A + , highlighting the relevance of choosing the most suitable charge-carrying species for this application.…”
Section: Introductionmentioning
confidence: 99%
“… 1 These charge-carrying species can also affect intrinsic properties of the sample molecules, as previously reported for a range of compound classes such as carbohydrates, 2 glycans and glycopeptides, 3 steroids, 4 fullerenes, 5 and macrocycles. 5 , 6 For example, Kellner et al showed that the formation, disassembly, and stability of crown ether fullerene dimers depend on the size of the alkali metal cations used, which was attributed to different binding sites. 5 Rister et al used IM-MS to separate isobaric steroids and reported varying CCS resolutions for different A + , highlighting the relevance of choosing the most suitable charge-carrying species for this application.…”
Section: Introductionmentioning
confidence: 99%
“…However, IMS-MS is still highly underexploited in the field of synthetic cages or macrocycles and their host : guest chemistry. [34][35][36][37][38][39][40][41][42][43] Herein, a combination of MS methods (single-stage, collision induced dissociation (CID) and IMS-MS experiments), fluorescence spectroscopy, NMR as well as molecular modelling of the supramolecular complexes of the Cy cages and the peptide EYE is reported to decipher the intimate details of the binding event, both in aqueous solution and in the gas-phase.…”
mentioning
confidence: 99%
“…We reported the helium CCS to directly compare our results with their data (see also Table S2). The calculations were done using the following linear approximation described by eq CCS normalN 2 = CCS He × 1.091 + 53.9 …”
Section: Resultsmentioning
confidence: 99%
“…The calculations were done using the following linear approximation described by eq 2. 50 = × + CCS CCS 1.091 53.9…”
Section: Direct Sampling Of Pancreatic Hormones From Single Mouse Isletsmentioning
confidence: 99%